Improvement of skin texture and wrinkles using radiofrequency ultra‐thin electrode technology. (12th December 2019) - Gold, Michael H.; Biron, Julie; Wilson, April
Abstract: Background: Application of radiofrequency (RF) energy with microneedles to facial skin shown to promote skin renewal. Aim: To evaluate the safety and efficacy of the VoluDerm technology with 100 ultra‐thin electrodes gen100 tip for improvement of skin texture and wrinkles. Methods: A prospective, open‐label, intra‐individual‐controlled trial. Twelve subjects (mean age, 45.5; Fitzpatrick skin types II‐III) with Fitzpatrick Elastosis Scale (FES) score 3‐6 were treated with VoluDerm RF technology using the gen100 ultra‐thin electrodes disposable tip. The participants underwent three treatments at 3‐week intervals. Treatment safety was evaluated at each treatment visit and at the follow‐up visits (1 and 3 months post last treatment). Efficacy of treatment evaluated at 1 and 3 months after the last treatment using the FES as well as evaluator‐ and subject‐rated Global Aesthetic Improvement Scale (GAIS). Results: Treatment was well tolerated, with no downtime or adverse events. One and three months after the last treatment session, physician‐rated FES showed statistically significant improvement of 2.67 ± 1.18 and 2.33 ± 1.03, respectively ( P < .0001), from baseline (4.83 ± 0.69). According to the investigator assessment of improvement using the GAIS scale, all subjects had an improvement in skin texture and pigmentation and most of the patients (91.7%) had an improvement in skin brightness, tightness, and wrinkles. Conclusion: This is the first study evaluating the Legend+ RF System with VoluDerm technology using the novel gen100 ultra‐thin electrodes tip. This study demonstrated effective and well‐tolerated treatment for improving skin texture and appearance with minimal to no downtime.